2016
DOI: 10.1371/journal.pone.0145486
|View full text |Cite
|
Sign up to set email alerts
|

Variations in ORAI1 Gene Associated with Kawasaki Disease

Abstract: Kawasaki disease (KD; MIM#61175) is a systemic vasculitis syndrome with unknown etiology which predominantly affects infants and children. Recent findings of susceptibility genes for KD suggest possible involvement of the Ca2+/NFAT pathway in the pathogenesis of KD. ORAI1 is a Ca2+ release activated Ca2+ (CRAC) channel mediating store-operated Ca2+ entry (SOCE) on the plasma membrane. The gene for ORAI1 is located in chromosome 12q24 where a positive linkage signal was observed in our previous affected sib-pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 51 publications
2
43
0
Order By: Relevance
“…16 Importantly, polymorphisms in 3 calcium pathway genes, ITPKC, ORAI1, and SLC8A1, have now been validated to be associated with KD susceptibility and aneurysm formation. 17,18 The ITPKC rs28493229 was excluded from the pathway analysis to avoid false-positive results because of the strong association of ITPKC with KD. We were unable to confirm an association with the ORAI1 rs3741596 reported in Japanese cohorts because of the low (<1%) risk allele frequency of the ORAI1 SNP in individuals of European and Hispanic descent.…”
Section: Calcium Signaling Pathways In Kdmentioning
confidence: 99%
“…16 Importantly, polymorphisms in 3 calcium pathway genes, ITPKC, ORAI1, and SLC8A1, have now been validated to be associated with KD susceptibility and aneurysm formation. 17,18 The ITPKC rs28493229 was excluded from the pathway analysis to avoid false-positive results because of the strong association of ITPKC with KD. We were unable to confirm an association with the ORAI1 rs3741596 reported in Japanese cohorts because of the low (<1%) risk allele frequency of the ORAI1 SNP in individuals of European and Hispanic descent.…”
Section: Calcium Signaling Pathways In Kdmentioning
confidence: 99%
“…Tsukahara et al (19) demonstrated that methylenetetrahydrofolate reductase gene polymorphism has an effect on the development of a coronary artery aneurysm. Onouchi et al (20) reported that the frequen- cy of the allele of rs3741596 in ORAI1 gene is >20 times higher in Japanese compared with Europeans and alterations have an association with KD. For this reason, more studies are required to explain the probable genetic predisposition in different ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…40 However, from its still high cost, GWAS for such low-frequency variants requiring whole-exome sequencing (WES) or whole-genome sequencing (WGS) has not become widely available. Therefore, at this moment, as coincidence of rare and common susceptible variants in the same genes experienced for ORAI1 15 and TLR6 17 is suggesting, target resequencing of a susceptibility gene panel might be a cost-effective way to identify novel rare susceptibility variants. Genome-wide searches by WES or WGS would be more successful when cases with extreme phenotypes are the targets.…”
Section: Involvement Of Rare Variants and Mutationsmentioning
confidence: 99%
“…12 In the subsequent case-control association studies, inositol 1,4,5-trisphosphate 3-kinase C (ITPKC), 13 caspase-3 (CASP3) 14 and calcium release-activated calcium modulator 1 (ORAI1) 15 genes located within the candidate regions were identified as susceptibility genes for KD. Another genome-wide linkage study using SNPs as genetic markers identified five chromosomal regions with suggestive evidence of linkage (LOD score > 3.0).…”
Section: Studies For Identifying Genetic Factors Of Kd Family-based Smentioning
confidence: 99%
See 1 more Smart Citation